Asset dynamics in Northern Nigeria - Dillon, Andrew; Quiñones, Esteban J. (International Food Policy Research Institute, 2010)
This paper examines household asset dynamics and gender-differentiated asset inequality over a 20-year period (1988-2008) in northern Nigeria. We show that the initial endowments of both household capital and livestock holdings are inconsistent with the poverty trap hypothesis but that tracking rules for households in panel surveys may lead to differences in empirical results on poverty traps. We also investigate whether initial household endowments contributed to gender-differentiated future asset levels and asset inequality. Initial livestock holdings have an effect on women's future livestock holdings but not on their livestock shares within the household, as the effect of initial livestock holdings on men's future livestock levels was much greater than its effect on women's levels. The mechanism through which asset levels differed was related to the relative prices of the assets in gender-differentiated asset portfolios. Men, who primarily held larger livestock with larger unit values, benefited from large price increases in high-value livestock, while women held lower-value livestock. These price fluctuations reinforced gender asset inequality within households for both types of assets considered.